REFRAMING THE DEATH OF THE MARITAL RELATIONSHIP AS AN OPPORTUNITY FOR GROWTH: A PROGRAMME FOR FACILITATING POST-DIVORCE ADJUSTMENT - Aspalan, Assim Hashim (Social Work/Maatskaplike Werk, 2018)
Divorce, symbolically speaking, may be viewed as the “death” of a marital relationship. During post-divorce guidance the counsellor should, amongst other things, allow the divorcee to mourn this relationship loss, facilitate a process where the dissolution of marriage is reframed to unearth opportunities for constructive and personal growth, and to support the divorcee in terms of healthy post-divorce adjustment. This paper proposes a programme for facilitating post-divorce adjustment. Schlossberg’s Transition Process Model (1981) is adopted, amongst others, as foundational framework informing the subject matter of the post-divorce guidance programme with the foci of this programme being informed by and based on the post-divorce recovery groups facilitated by the author